A bibliometric analysis of research publications funded partially by the Cancer Association of South Africa (CANSA) during a 10-year period (1994–2003) - Carl F. Albrecht (South African Family Practice)
Background: The objective of this study was to establish the quantity and quality of research publications outputs by grant recipients of the Cancer Association of South Africa (CANSA) over a 10-year period (1994–2003).